EVALUASI PELATIHAN (TRAINING) LEVEL II BERDASARKAN TEORI THE FOUR LEVELS KIRKPATRICK - umi Widiyastuti; Dedi Purwana ES. (Faculty of Economics, State University of Jakarta., 2015)
Training is an important aspect in human resources development (HRD) in the organization, as an effort to improve knowledge, skills, and expertise. It should be organize effectively in accordance with the needs of the organization’s member.This research was conducted to evaluate the training for students organized by Pusat Sumber Belajar Universitas Negeri Jakarta (PSB UNJ); and it aimed to find out the effectiveness of training at level II, based on the theory of Four Levels Kirkpatrick. The training that we observed in this study includingtraining of scientific approach learning, training of project-based learning, training of internet based learning, training of simple medium and training of authentic assessment. Population in this study is all students who participate in these programs that came from the entire faculty in UNJ. Using purposive sampling, the sample is randomly selected proportionately based on the type of training provided by PSB UNJ. The number of samples obtained is 110 students.By comparing pre and post-testdata using paired samples t-test, the resultsshown that there are significant difference in knowledge and skills before and after attending the training.